Evaluation of anxiolytic potential of Cichorium Intybus methanolic root extracts - S.Tripathy; N.K.S Neeraja (Journal of Biomedical and Pharmaceutical Research, 2020)
Cichorium Intybus L. is a medicinally important plant that belongs to the family Asteraceae. The plant root is used as anti-hepatotoxic, antiulcerogenic, antiinflammatory, appetizer, digestive, stomachic, liver tonic, cholagogue, cardiotonic, depurative, diuretic, emmenagogue, febrifuge, alexeteric and also as tonic. The present study was carried to screen the anxiolytic potential of Cichorium Intybus L methanolic root extracts by using different animal models like actophotometer, rotarod, staircase, holeboard, elevated plus maze tests . In the experiment the extracts found to decrease the anticipatory anxiety of the animal without significant alteration in motor coordination. Efficacy may be attributed to the presence of different phytochemicals like coumarins, flavonoids in the extracts.